KARAKTERISTIK FISIKO-KIMIA, MIKROBIOLOGI DAN SENSORI SELAI JAMBU BIJI MERAH ASAL PULAU TIMOR, NUSA TENGGARA TIMUR YANG DITAMBAHKAN AGAROSA - Lince Mukkun; Yuliana Tandirubak; Herianus J.D. Lalel; Mersiana Darti (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
This study aims to determine the effect of the percentage of agarose in the physico-chemical, microbiological and organoleptic properties of the right amount of flour gelatin addition on the manufacture of local red guava jam and find out the right percentage of agarose to produce quality red guava jam products. This study used a Complete Randomized Design (RAL) with 5 treatments of gelatinous addition of flour (0%, 1%, 1.5% and 2%) with 3 repeats. The results were analyzed statically using ANOVA and further testing of Ducan's New Multiple at a level of 5%. For organoleptic data using the Friedman test and the Least Significant Difference (LSD) advanced test. The parameter for the observed physical properties of the jam is texture. Parameter for the chemical properties of jam observed is water content, sugar content, and vitamins while the observed microbiological parameters are calculating the total microbes. Organoleptic parameter for organoleptic test i.e. aroma, taste, texture and color. The results of this study show that the addition of agarose has a significant effect on physico-chemical properties, namely texture, water content, sugar content, vitamin C, total microbes and organoleptic tests, namely color and texture. Based on physical, chemical, microbiological and organoleptic analysis, the best product was obtained, namely with the addition of gelatin powder 1.5%. The score of the values obtained in the organoleptic test was a score of aroma (4.30 likes), taste (4.12), texture (4.40) and color (4.40). The value of the physical properties analysis is 359 grams of texture. While the chemical analysis is water content of 14.9%, sugar content of 21.2%, vitamin C of 10.48 mg and analysis of total microbes, which is 0.66 x 10 2 CFU / mL.